2020
DOI: 10.2147/ppa.s274634
|View full text |Cite
|
Sign up to set email alerts
|

<p>Self-Medication Practice and Associated Factors Among University of Gondar College of Medicine and Health Sciences Students: A Cross-Sectional Study</p>

Abstract: Purpose Self-medication is the use of medicines by individuals to treat self-recognized illnesses or symptoms without any medical supervision. Such practices may cause antimicrobial resistance, which causes treatment failure, economic loss, serious health hazards, missed diagnosis, delayed appropriate treatment, drug dependency, and adverse drug effects. However, empirical evidence is limited to the current status of its practices and associated factors among university students. Thus, the aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 27 publications
2
34
0
2
Order By: Relevance
“…A study by Esan ( Esan et al, 2018 ) found that about 71% of the students self-medicated with antibiotics and analgesics. Studies by Zeru ( Zeru et al, 2020 ) in Ethiopia and Hashemzaei ( Hashemzaei et al, 2021 ) in Iran found a similar self-medication prevalence rate of about 50% among university students. In these studies, fever and headache were the most reported common complaint related to self-medication.…”
Section: Introductionmentioning
confidence: 73%
“…A study by Esan ( Esan et al, 2018 ) found that about 71% of the students self-medicated with antibiotics and analgesics. Studies by Zeru ( Zeru et al, 2020 ) in Ethiopia and Hashemzaei ( Hashemzaei et al, 2021 ) in Iran found a similar self-medication prevalence rate of about 50% among university students. In these studies, fever and headache were the most reported common complaint related to self-medication.…”
Section: Introductionmentioning
confidence: 73%
“…Study participants were recruited from both sex having health and non-health backgrounds, the studies were adequately addressed the total population of catchment area to select the sample size as they have used appropriate sampling method. Accordingly, the minimum sample size was 250 [ 27 ] and the maximum was 772 [ 28 ]. The lowest prevalence (19.8%) of self-medication was reported in studies conducted in Gondar University, Amhara region [ 29 ], whereas the highest prevalence (77.01%) was reported in a study conducted in Arsi University, Oromia region [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…To show the association between self-medication and sex of patients, eight studies [ 24 , 28 , 30 34 , 38 ] were selected for meta-analysis. Two studies [ 28 , 30 ] showed, there was a statistically significant association between self-medication and sex and six studies showed that there was no significant association between medication self-practice and sex of the respondents. The pooled finding of the analysis showed that there was no significant association between medication self-practice and the sex of the students.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation is that males may have faced more fungal infections than their female counterparts which resulted in higher SM practices. In contrast, studies in Saudi Arabia, 6 Ethiopia, 28 and Ghana 32 found relatively higher rates of SM among females and justified these findings by stating that females have relatively lower immunities than males and also probably have a greater need for pain-killers due to the monthly attacks of dysmenorrhea. Also, we found that students that were interested in following social media drug advertisements had practiced SM more significantly than their peers (COR=0.5, 95% CI=0.3–0.8, P<0.05), which could be explained by the high influence of advertisements on the attitudes and behavior of this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Irrational use of drugs for SM is a worldwide public health problem which results in treatment failure, economic loss, and increased burden of morbidity and mortality. 28 The understanding of consumer characteristics associated with SM is crucial for proper planning of public health awareness efforts and the implementation of effective management strategies. Additionally, searching the literature revealed that the prevalence of fungal infections in Egypt is alarming.…”
Section: Discussionmentioning
confidence: 99%